STAT3- and GSK3β-mediated Mcl-1 regulation modulates TPF resistance in oral squamous cell carcinoma. (3rd November 2018) - Maji, Santanu; Shriwas, Omprakash; Samal, Sabindra K; Priyadarshini, Manashi; Rath, Rachna; Panda, Sanjay; Das Majumdar, Saroj Kumar; Muduly, Dillip Kumar; Dash, Rupesh
Abstract : Among all antiapoptotic members, Mcl-1 is an important survival factor for TPF-resistant oral squamous cell carcinoma (OSCC). Signal transducer and activator of transcription 3 (STAT3) and glycogen synthase kinase 3 beta (GSK3β) modulate Mcl-1 expression in chemoresistant OSCC cells. Mcl-1 inhibition by Triptolide restores chemotherapy-induced cell death in patient-derived xenograft from chemo non-respondent OSCC. Abstract: Cisplatin alone or in combination with 5FU (5-fluorouracil) and docetaxel (TPF) are common regimen chemotherapeutics for treatment of advanced oral squamous cell carcinoma (OSCC). Despite the initial positive response, several patients experience relapse due to chemoresistance. The potential role of Bcl-2 antiapoptotic members in acquired chemoresistance is yet to be explored. To address this, we designed two different relevant OSCC chemoresistant models: (i) acquired chemoresistant cells, where OSCC lines were treated with conventional chemotherapy for a prolonged period to develop chemoresistance, and (ii) chemoresistant patient-derived cells, where primary cells were established from tumor of neoadjuvant-treated OSCC patients who do not respond to TPF. Among all Bcl-2 antiapoptotic members, Mcl-1 expression (but not Bcl-2 or Bcl-xL) was found to be upregulated in both chemoresistant OSCC lines and chemoresistant tumors when compared with their respective sensitive counterparts. Irrespective of all three chemotherapy drugs, Mcl-1 expression was elevated in OSCC cells that are resistant to either cisplatin or 5FU or docetaxel. In chemoresistant OSCC, Mcl-1 mRNA was upregulated by signal transducer and activator of transcription 3 (STAT3) activation, and the protein was stabilized by AKT-mediated glycogen synthase kinase 3 beta (GSK3β) inactivation. Genetic (siRNA) or pharmacological (Triptolide, a transcriptional repressor of Mcl-1) inhibition of Mcl-1 induces drug-mediated cell death in chemoresistant OSCC. In patient-derived xenograft model of advanced stage and chemoresistant OSCC tumor, Triptolide restores cisplatin-mediated cell death and facilitates significant reduction of tumor burdens. Overall, our data suggest Mcl-1 dependency of chemoresistant OSCC. A combination regimen of Mcl-1 inhibitor with conventional chemotherapy deserves further clinical investigation in advanced OSCC.